Dynamic Calibration of a Strain Gauge Based Handlebar Force Sensor for Cycling Purposes. (2015) - Vanwalleghem, Joachim; De Baere, Ives; Loccufier, Mia; Van Paepegem, Wim
Abstract: Dynamic measurements on bicycles are implemented for assessing the vibration comfort of the cyclist or for the measuring the load distribution at bicycle components. Accelerometers are typically used for comfort evaluation, force sensors are selected for comfort and load measurements. For cycling purposes, typically custom made, strain gauge based, are designed. These sensors are implemented for static and dynamic load measurements. When force transducers are used for dynamic measurements, it is important to have detailed knowledge of the dynamic properties of the force transducer and the corresponding electronic measuring equipment, as considerable errors can occur under dynamic conditions. Moreover, the arrangement of the force transducer, the mounting conditions and the whole mechanical structure of the measuring arrangement may significantly influence the uncertainty of dynamic force measurement. This is investigated for a strain gauge based handlebar force sensor. The dynamic calibration procedure assesses the amplitude sensitivity, the phase response and the seismic mass. It is observed that (i) in-situ boundary conditions significantly reduce the expected behavior calculated from idealized clamped boundary conditions and (ii) the dynamic force sensor properties are different from the DC properties. As a result from the dynamic calibration procedure, the developed handlebar force sensor can be used in the frequency range from DC to 35 Hz.